The Influence of Psychological Capital and Workload on Personnel Performance Mediated by Work Engagement at the TNI AD Infanteri Education Center - Amos Herman Kune; Hariandy Hasbi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study examines the effect of psychological capital and workload on the performance of officers and non-commissioned officers at the Indonesian Army Infantry Education Center, with work engagement as a mediating variable. An explanatory quantitative survey approach was conducted on 100 trainers using total sampling and a five-point Likert scale questionnaire. The analysis used linear regression and mediation tests. The results show that psychological capital and workload have a significant effect on performance and work engagement, while work engagement has no effect and does not mediate performance. These findings confirm that trainer performance is more directly determined by psychological capital and workload, so that strengthening psychological capital and effective workload management are important in professional military education.